"Did I Choose a Birth Control Method Yet?": Health Care and Women's Contraceptive Decision-Making. (January 2022) - Manzer, Jamie L.; Bell, Ann V.
In the United States, unintended pregnancy is medicalized, having been labeled a health problem and "treated" with contraception. Scholars find women's access to contraception is simultaneously facilitated and constrained by health care system actors and its structure. Yet, beyond naming these barriers, less research centers women's experiences making contraceptive decisions as they encounter such barriers. Through in-depth, semi-structured interviews with 86 diverse, self-identified women, this study explores how the medicalization of unintended pregnancy has influenced women's contraceptive access and decision-making. We highlight the breadth of such influence across multiple contraceptive types and health care contexts; namely, we find the two most salient forces shaping women's contraceptive decisions to be their insurance coverage and providers' contraceptive counseling. Within these two categories, we offer crucial nuance to demonstrate how these oft-cited barriers implicitly and explicitly influence women's decisions. Paradoxically, it is the health care system, itself, that both offers yet constrains women's contraceptive decisions.